Functionalized Metal–Organic Frameworks for the Efficient Removal of Low Concentrations of Ammonia. Issue 2 (9th November 2015) - Li, Libo; Wang, Yong; Yang, Jiangfeng; Chen, Yang; Li, Jinping
Abstract: The excellent ammonia adsorption properties of [Cu(bpy)2 (OTf)2 ] n (ELM‐12; bpy=4, 4′‐bipyridine, OTf=trifluoromethanesulfonate) make it unique for the removal of ammonia at low concentrations, but its instability under humid conditions restrict its practical applications. Herein, a functionalized ELM‐12@PDMS (PDMS=polydimethylsiloxane) composite was prepared by coating a nanoscale PDMS layer on the ELM‐12 surface, which significantly increased its hydrophobicity. The dynamic ammonia adsorption properties of ELM‐12 and ELM‐12@PDMS were explored by means of kinetic breakthrough measurements under dry and humid conditions. ELM‐12@PDMS can effectively capture ammonia at 100 ppm when maintained under 80 % relative humidity, which makes it promising for real applications. Abstract : Damp‐proof MOF : A functionalized ELM‐12@PDMS composite has been prepared by coating a nano‐PDMS layer on the surface of ELM‐12; this significantly increased the hydrophobicity of ELM‐12. ELM‐12@PDMS can effectively capture ammonia at low concentrations (100 ppm) under 80 % relative humidity (see figure; ELM‐12=[Cu(bpy)2 (OTf)2 ] n, bpy=4, 4′‐bipyridine, OTf=trifluoromethanesulfonate, PDMS=polydimethylsiloxane).